Ascorbic acid triggered physiochemical transformations at different phenological stages of heat‐stressed Bt cotton. (20th April 2017) - Kamal, M. A.; Saleem, M. F.; Shahid, M.; Awais, M.; Khan, H. Z.; Ahmed, K.
Abstract: Heat stress at reproductive stages of cotton crop is the main cause for instability in yield than other abiotic stresses of crops. An experiment was conducted to observe the impacts of heat stress at squaring and flowering stages of cotton and potential of exogenously applied ascorbic acid to alleviate this stress. The experiment was planted for two consecutive years, that is 2013 and 2014, in randomized complete block design with split plot arrangement having three replications. Treatments were comprised of heat stress in main plots, viz. H0  = no heat imposition; H1  = heat imposition at square initiation; H2  = heat imposition at flower initiation and foliar‐applied ascorbic acid in subplots, viz. A0  = control or water spray; A1  = 20 mg/L; A2  = 40 mg/L; and A3  = 60 mg/L. Results showed that heat stress badly affected plant water relations (relative water contents and osmotic potential), total chlorophyll contents and activities of antioxidant enzymes that led to a corresponding decrease in seed cotton yield. Foliar application of ascorbic acid (40–60 mg/L) ameliorated adverse effects of heat and thus helped the crop to improve its water relations, stay green and antioxidant enzymes resulting into better crop yield.